Parasite diversity and microsatellite variability in native and introduced populations of four Neogobius species (Gobiidae) - Ondračková, M; Šimková, A; Civáňová, K; Vyskočilová, M; Jurajda, P (Parasitology, 2012)
Species introduced into new areas often show a reduction in parasite and genetic diversity associated to the limited number of founding individuals. In this study, we compared microsatellite and parasite diversity in both native (lower Danube) and introduced populations of 4 Ponto-Caspian gobies, including those (1) introduced from within the same river system (middle Danube; Neogobius kessleri and N. melanostomus), and (2) introduced from a different river system (River Vistula; N. fluviatilis and N. gymnotrachelus). Microsatellite data confirmed the lower Danube as a source population for gobies introduced into the middle Danube. Both native and introduced (same river system) populations of N. kessleri and N. melanostomus had comparable parasite species richness and microsatellite diversity, possibly due to multiple and/or continual migration/introduction of new individuals and the acquisition of local parasites. Reduced parasite species richness and microsatellite diversity were observed in introduced (different river system) populations in the Vistula. A low number of colonists found for N. fluviatilis and N. gymnotrachelus in the Vistula potentially resulted in reduced introduction of parasite species. Insufficient adaptation of the introduced host to local parasite fauna, together with introduction into an historically different drainage system, may also have contributed to the reduced parasite fauna.
Keywords: Biodiversity; Perciformes; mikrosatelitní repetice; Animals; Microsatellite Repeats; biodiverzita; genetická variace; zvířata; nemoci ryb; Fish Diseases; Genetic Variation